Amylase concentration and activity in the amniotic fluid of fetal rats with retinoic acid induced myelomeningocele. (2nd January 2022) - Sasso, Elizabeth B.; Thornton, Matthew E.; Chmait, Ramen H.; Ouzounian, Joseph G.; Grubbs, Brendan H.
Abstract: Background: In utero neurologic injury in myelomeningocele (MMC) occurs via a two-hit process: failed neural tube closure followed by neurodegeneration in utero . Meconium in the amniotic fluid contains pancreatic digestive enzymes and is neurotoxic in rat models of MMC. Objectives: The objectives of this study were to demonstrate the neurotoxicity of α-amylase and to compare the enzyme concentration and activity in the amniotic fluid of rats with retinoic acid induced MMC to a healthy control population. Study design: Timed pregnant Sprague Dawley rats were gavage fed all-trans retinoic acid (60 mg/kg) in olive oil on gestational day E10 to induce a MMC defect. Control rats received olive oil. Amniotic fluid was collected on embryonic days E15, E17, E19, and E21. The amniotic fluid amylase concentration and relative activity were measured at each gestational age, and levels were compared between the MMC and control groups using Wilcoxon Rank Sum and Kruskal–Wallis tests. In a subset of dams sacrificed on E10.5, neuroepithelial cells were isolated from control embryos and exposed to α-amylase in increasing concentrations. Percentage of cell survival was assessed with CellProfiler software. Results: Amniotic fluid amylase activity for embryonic days E15, E17, E19, and E21 was determined for MMC and control pups. Amylase activity increased significantly from E15 to E21 in both control ( p = 3.0 × 10 −5 ) and MMC ( p = 1.5 × 10 −5 ) groups. Relative amylase activity was significantly increased in MMC pups compared to controls on E19 (247, 792.8 versus 106, 263.6; p = .0019) and E21 (772, 645.8 versus 481, 975.3; p = .021); no difference was detected on E15 (36, 646.8 versus 40, 179.3; p = .645) or E17 (121, 617.5 versus 71, 750; p = 1.000). In vitro, amylase demonstrated dose-dependent toxicity to fetal rat neuroepithelial cells. Conclusion: Amylase concentration and activity level were higher in the amniotic fluid of rats with retinoic acid induced MMC compared to controls with advancing gestational age. As amylase is toxic to neural epithelial cells, the higher activity of this digestive enzyme in fetuses with MMC may be a contributor to neural tube damage in utero . Future research should focus on amylase and other digestive enzymes in human MMC, as they may serve as potential targets of in utero therapy.